153k views
5 votes
Perform each indicated operation

Perform each indicated operation-example-1
User Amin Sh
by
5.1k points

1 Answer

2 votes

Answer:
(x+6)/(x-4)

Explanation:

First you need know some general formuals of factorization such as


x^3+y^3=(x+y)(x^2-xy+y^2) so you have
x^3+64=X^3+4^3=(x+4)(x^2-4x+4^2)

And,
x^2-y^2=(x-y)(x+y) so you have
2x^2-32=2(x^2-16)=2(x^2-4^2)=2(x+4)(x-4)

If you use them, then you can modify your equations such as


(x^3+64)/(2x^2-32) ÷
(x^2-4x+16)/(2x+12) =
((x+4)(x^2-4x+4^2))/(2(x+4)(x-4)) ÷
(x^2-4x+16)/(2(x+6)) =
((x+4)(x^2-4x+4^2))/(2(x+4)(x-4)) . \frac{2(x+6)}{{x^2-4x+16}} = (1)/(x-4).(x+6)/(1)=(x+6)/(x-4)

User Krupesh Kotecha
by
4.9k points